Does conditionality work?: a test for an innovative US aid scheme - Öhler, Hannes; Nunnenkamp, Peter; Dreher, Axel (European economic review, 2011)
Performance-based aid has been proposed as an alternative to the failed traditional approach whereby donors make aid conditional on the reform promises of recipient countries. However, hardly any empirical evidence exists on whether ex post rewards are effective in inducing reforms. We attempt to fill this gap by investigating whether the Millennium Challenge Corporation (MCC) was successful in promoting better control of corruption. We employ a difference-in-difference-in-differences (DDD) approach, considering different ways of defining the treatment group as well as different time periods during which incentive effects could have materialized. We find evidence of strong anticipation effects immediately after the announcement of the MCC, while increasing uncertainty about the timing and amount of MCC aid appears to have weakened the incentive to fight corruption over time.
Gesehen am 16.11.2017